2020
DOI: 10.3389/fmars.2020.00696
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Seagrass Carbon Stocks Between Tropical Estuarine and Marine Mangrove-Fringed Creeks

Abstract: Seagrass and associated blue carbon ecosystems are important carbon sinks, and hence understanding their spatial and temporal variability is vital in appreciating their potential roles in climate change mitigation and adaptation. The Indo-Pacific region has the highest seagrass biodiversity, yet little focus has been made to compare seagrass habitat extent and carbon dynamics with their temperate counterparts. The present study assessed habitat characteristics and seagrass species distribution, diversity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
3
16
1
Order By: Relevance
“…Ea, Cym/Th and Tc) constituted the focal habitats of this study due to their wide distribution (Gullström et al 2002) and high potential as carbon sinks in the western Indian Ocean region (e.g. Githaiga et al 2017;Gullström et al 2018;Juma et al 2020). The bay also contained vast scattered sandy areas with low densities of intermixed small-sized seagrasses belonging to the Fig.…”
Section: Study Sitementioning
confidence: 99%
“…Ea, Cym/Th and Tc) constituted the focal habitats of this study due to their wide distribution (Gullström et al 2002) and high potential as carbon sinks in the western Indian Ocean region (e.g. Githaiga et al 2017;Gullström et al 2018;Juma et al 2020). The bay also contained vast scattered sandy areas with low densities of intermixed small-sized seagrasses belonging to the Fig.…”
Section: Study Sitementioning
confidence: 99%
“…Ecological connectivity between seagrass and mangroves is a multifaceted process and plays an important role in the ecological functioning of coastal ecosystems (Berkström et al 2020;Mishra and Apte 2020;Carlson et al 2021). This connectivity between seagrass and mangrove ecosystems positively influences the carbon storage capacity in the seagrass ecosystems (Juma et al 2020;Asplund et al 2021). The present study quantified the carbon storage in ecologically connected seagrass and mangrove ecosystems in a tropical island (ANI) ecosystem and observed that seagrass meadows adjacent to mangrove ecosystems store a higher amount of carbon in their sediment and biomass compared to seagrass ecosystems without mangroves.…”
Section: Discussionmentioning
confidence: 76%
“…To determine the amount of carbon in the two seagrass meadows, the carbon stocks for each species was summed up for each site and the sum multiplied by the sampling area (Juma et al, 2020). The variabilities and errors associated with the measurements were determined by calculating the standard error for each species at each site and multiplying by the area of the sampling site (Juma et al, 2020).…”
Section: Sediments and Biomass Sample Collectionmentioning
confidence: 99%
“…Seagrass meadows consist of different species that vary in size, form, growth and turnover rates, and may be persistent or transitory (Kilminster et al, 2015). As a result, carbon sequestration in seagrass meadows vary in different regions (Lavery et al, 2013;Serrano et al, 2018) and within meadow landscapes themselves (Gullström et al, 2018;Ricart et al, 2017;Juma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%